ON LEGAL CONSEQUENCES OF JUDGEMENTS OF THE POLISH CONSTITUTIONAL TRIBUNAL PASSED BY AN IRREGULAR PANEL - Radziewicz, Piotr (Review of European and Comparative Law, 2017)
Recent years have gone down in the history of the Polish constitutional thought with an unprecedented dispute concerning the underlying principles for the activity and statutory position of the Constitutional Tribunal (‘CT’) . Under the dynamics of political events following the 2015 parliamentary elections the initial doubts whether some of the CT judges were appointed correctly turned into the deepest constitutional crisis in the modern history of Poland which ultimately led to decomposition of the entire state system of constitutional control. Finding all of the underlying causes of that crisis would require multifaceted analyses carried out by experts representing various scientific disciplines. Such an undertaking goes far beyond the boundaries of this study. The aim of this sketch is to reconstruct one of the episodes of the so-called Constitutional Tribunal Crisis which is a direct outcome of the appointment of CT judges by the Sejm (Parliament) to replace judges whose terms did not yet expire . This issue is of key importance for the current discussions on the nature and consequences of CT judgments . The presence of unauthorized persons in CT adjudicating panels became also an important symbolic turning point in the systemic transformation of the Polish constitutional court at the beginning of 2017 .